Development of Sewa Dance Performers at Sanggar Talago Biru Nagari Pitalah Batipuh Sub-district Tanah Datar Regency - Herlinda; A’isiyah, Zamratul (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This study aims to describe and reveal the development of Sewa dance actors in Sanggar Talago Biru Nagari Pitalah, Batipuh District, Tanah Datar Regency. This type of research is qualitative research with a descriptive analysis method. The instrument in this research is the researcher himself and is assisted by supporting instruments such as stationery, a camera, and a flash drive. The data in this study used primary and secondary data. Data collection techniques were carried out by means of library studies, observation, interviews, and documentation. The steps of analysing data are collecting data, describing data, and concluding data. The results showed that sewa dance is a traditional dance that developed in the Talago Biru Studio, Jorong Jambak Nagari Pitalah, where this dance has not been danced for a long time. Talago Biru Studio was developed by interviewing Tuo Dance, the owner of Talago Biru Studio, and asking permission from the Wali Nagari. Rental dance actors are usually played by two actors, namely the dance tuo and his Sapaguruan friends. The development carried out at the Talago Biru studio consisted of eight meetings, where at the first meeting the dance actors consisted of four men. At the second meeting, the number of Sewa dance actors increased to 2 people, so that the total number of Sewa dance actors totaled 6 people. In the third and eighth meetings, the Sewa dance actors conducted training by continuing and repeating the movements that had been taught by the dance teacher. However, until now, there have not been female actors playing sewa dance because the traditional customs in Nagari Pitalah do not have women playing silat. Therefore, the traditional customs of Nagari Pitalah silat actors are only played by men.